Metabolic Syndrome (MetS) as a Predictor of Fatty Liver in HIV Infected Adults from the Miami Adult Studies on HIV (MASH) Cohort (FS12-06-19). (13th June 2019) - Teeman, Colby; Huang, Yongjun; Liu, Qingyun; Hernandez, Jacqueline; Tamargo, Javier; Jasmin, Juphshy; Seminario, Leslie; Clayton, Priscilla; Zarini, Gustavo; Martinez, Sabrina; Campa, Adriana; Piperato, Joseph; et al.
Abstract: Objectives: One of the major comorbidities among people living with HIV (PLWH) is liver disease. MetS is common in this population and may also play a role in the development of liver disease. In order to better understand the mechanisms of liver disease in PLWH, it is important to investigate the relationship between components of MetS and the risk of fatty liver, an early precursor to liver disease. The objective of this study was to determine if the 5 criteria used to diagnose MetS contribute to liver steatosis. Methods: Crossectional analyses of data from the MASH cohort were analyzed. Waist circumference (WC) and blood pressure (BP) were measured by a research nurse. Serum triglycerides (TRG), glucose (GLU), and HDL were determined in fasting by LabCorp. Liver fat % was estimated with proton density fat fraction using Magnetic Resonance Elastography conducted on a 3T Siemens MAGNETOM Prisma MRI. Liver fat >5% was defined as stage 1 steatosis. Components of MetS were taken from the NCEP ATP III definition of MetS. Spearman correlations and logistic regression were used for analyses. Results: A total of 324 PLWH aged 53.5 ± 7.5 years were included. Liver fat% was correlated with WC ( r  = 0.394, P  < 0.001), TRG ( r  = 0.332, P  < 0.001), GLU ( r  = 0.358, P  < 0.001), and systolic BP ( r  = 0.183, P  = 0.011), inversely correlated with HDL ( r  = −0.236, P  = 0.001), and trended toward significance with diastolic BP ( r  = 0.133, P  = 0.065). Participants with stage 1 steatosis had a larger WC (41.02in ± 5.3 vs 36.95 ± 5.5, P  = 0.001), higher TRG (210.3 mg/dL ± 173.9 vs 121.3 ± 67.9, P  = 0.002), and higher GLU (126.1 mg/dL ± 77.7 vs 93.92 ± 50.8, P  = 0.001) than those without steatosis. No significant difference was found for HDL cholesterol, SBP, or DBP. A logistic regression model that included all 5 MetS criteria and was controlled for age, gender, and alcohol AUDIT score >8 found that WC (OR 1.11, 95% CI 1.01–1.23, P  = 0.030), TRG (OR 1.01, 95% CI 1.00–1.01, P  = 0.040), and GLU (OR 1.01, 95% CI 1.00–1.03, P  = 0.033) are significant predictors of stage 1 steatosis. Conclusions: WC, TRG, and GLU, three of the 5 criteria for diagnosing MetS were significant predictors of stage 1 steatosis in PLWH. Future studies investigating the risk of liver disease progression in PLWH need to account for these confounding factors as they explore HIV specific mechanisms for liver disease. Funding Sources: National Institutes on Drug Abuse #5UO1DA040381.